Chemical composition and evaluation of prolyl oligopeptidase and acetylcholinesterase inhibitory activities of Leonurus Sibiricus L. from Brazil. Issue 12 (18th June 2017) - Zachow, Lucimara L.; Ávila, Janaína M.; Saldanha, Geovane A.; Mostardeiro, Marco A.; da Silva, Ubiratan F.; Morel, Ademir F.; Dalcol, Ionara I.
Abstract: Chemical investigation of the aerial parts of Leonurus sibiricus L. used in Brazilian folk medicine led to the identification of the following constituents: the labdane-type diterpenoid leojaponin, the phytosterols β-sitosterol and β-sitosterol glucoside and the alkaloid leonurine. The crude extracts obtained from methanol and methanol/1% HCl and pure compounds isolated from L. sibirius were investigated as acetylcholinesterase (AChE) and prolyl oligopeptidase (POP) inhibitors. Extracts obtained by maceration were active against POP (53–58%), but showed weak activity against AChE. The isolated leojaponin and leonurine were evaluated as POP inhibitors. Abstract :